Population Status of Napoleon Wrasse (Cheilinus undulatus) at Bando Island, West Sumatra - Fadhlan Basiluddin Rahmat; Nur Jasilah; Samsuardi Samsuardi; Andreas Kunzmann (Journal of Marine Research, 2026)
The Pieh Marine Protected Area (MPA) in West Sumatra serves as a critical habitat for the endangered Napoleon wrasse (Cheilinus undulatus), a species listed under CITES Appendix II and nationally protected in Indonesia. Reports from local communities suggested the reappearance of this species at Bando Island after years of presumed absence. This study aims to assess the current status and potential recovery of Napoleon wrasse populations within the island’s core conservation zone. Field surveys conducted in June 2024 used a GPS-based underwater visual census (UVC) to estimate population density and theoretical stock size. Two individuals a juvenile (~20 cm) and an adult (~60 cm) were recorded along a total transect area of 6.64 ha, resulting in a density of 1 individual/ha and a theoretical stock of 0.035 individual across the island’s 28 ha coral reef area. Habitat assessment revealed moderate live coral cover (40%) and high substrate heterogeneity, including dead coral, rubble, and sand, which provide structural complexity, favourable for reef fish. However, the observed density falls within the “very low” category of the national conservation scale, indicating a severely depleted population. These findings suggest that despite suitable habitat conditions, the Napoleon wrasse population remains critically low and functionally vulnerable. Immediate conservation actions such as establishing no-take zones, restoring coral habitats, enhancing monitoring, and regulating the live reef fish trade are recommended to enable natural recolonization and recovery of this iconic species within the Pieh MPA.